Exploring the genetic architecture underlying dietary fiber content in Colombian Andean blueberry (Vaccinium meridionale Swartz) - Ginna Patricia Velasco Anacona; Angie Carolina Guevara Correa; Carlos-Eduardo Narváez-Cuenca; Teresa Mosquera Vásquez; Johana Carolina Soto Sedano (PLoS ONE, 2026)
Dietary fiber composition is a major determinant of fruit nutritional quality, yet its genetic basis remains poorly characterized in wild Vaccinium species. Here, we combined extensive phenotyping with a genome-wide association study (GWAS) to dissect the genetic control of dietary fiber traits in Colombian agraz ( Vaccinium meridionale Swartz). Total dietary fiber (TDF), insoluble dietary fiber (IDF), and soluble dietary fiber (SDF), the SDF/IDF ratio, and maturity index (MI) were quantified in fruits from 119 genotypes, representing the most comprehensive evaluation of dietary fiber fractions in fresh Vaccinium fruit to date. Using a GWAS approach based on 16,709 high-quality SNPs across 69 genotypes, we identified 24 QTLs associated with dietary fiber content across 15 chromosomes, revealing a polygenic architecture underlying this trait. A TDF QTL (Chr41:26883013) directly co-localized with VaccDscaff31-augustus-gene-268.33 , a 7-deoxyloganetin glucosyltransferase, embedded within a glycosyltransferase-rich LD block. IDF variation was associated with VaccDscaff33-processed-gene-116.2 (pectin methylesterase 15) while the SDF/IDF ratio co-localized with VaccDscaff55-augustus-gene-9.30 , encoding a xyloglucan endotransglucosylase/hydrolase. Together, the integration of high-resolution phenotyping with QTL mapping connects natural variation in dietary fiber content and composition to specific biosynthetic, remodeling, and regulatory pathways, providing actionable molecular targets for marker-assisted and genomic selection aimed at improving nutritional quality, texture, and processing traits in Vaccinium breeding programs.